Transformaciones en el espacio sociorresidencial de Monterrey, 1990-2000 - González Arellano, Salomón; Villeneuve, Paul (El Colegio de México A.C., 2007)
The aim of this article is to characterize the residential structure of the Metropolitan Area of Monterrey (MAM) and to identify the principal socio-spatial transformations that occurred in the 1990s. On the basis of the review of various papers concerning the analysis of the social space of certain Mexican and foreign cities, the principles of factorial ecology are applied for two main purposes: 1) to identify the principal dimensions structuring MAM’s socio-residential space and 2) to characterize the changes in the socio-residential structure of Monterrey for the period between 1990 and 2000. The results of this analysis reveal a degree of instability in the way socio-residential space is structured on the one hand, and a growing differentiation resulting from the polarization of the immigrant population in Monterrey’s urban space on the other.